(untitled) (Journal of Oriental Studies, 2023)
19th-century author, Archpriest Yeghishe (Hovakim) Geghamiants, who is also known to the Armenian reader as Haykuni, in 1885 traveled to Artsakh and published his work “Travelling Notes”. There are noteworthy mentions of the prevalence of Iranian culture and the Persian language in Shushi City in Geghamiants’s work. Thanks to the information given by Geghamiants about the Persian people living in Shushi at that time, we get an idea of what they were involved in and what role the Persians had in the life of the city, what relations they had with the neighboring Armenians. When speaking about the daily life of the local Armenian population, Geghamiants noted that Armenians also used to sing Persian songs during their happy events, Armenians used to participate in the wedding ceremonies of neighboring Persians, and vice versa. When speaking about some Armenian schools, the author mentioned that the Persian language was also taught in those schools. In his work, Geghamiants mentioned translating masterpieces of Persian literature into Armenian and publishing them in Shushi. Geghamiants referred to the Persian sanctuaries in Shushi and around the city, he refers to the pilgrimage sites visited by the Persians. The information presented by Geghamiants is often found in other sources too, but the work of Geghamiants stands out for its free and natural simplicity. In that sense, it is instructive and highly relevant to value and research the information provided by this source.